Rancang Bangun Sistem Monitoring dan Pendeteksi Lokasi Kebocoran Pipa Berdasarkan Analisis Debit Air Berbasis IoT - Prasetya, Ardi DwI; Haryanto, Haryanto; Wibisono, Kunto Aji (Elektrika, 2020)
The purpose of this research is to design and realize a pipe leak detection system that can be monitored with an Android application. Water flow sensor is used to determine the flow of water, with water flow rate analysis it is possible to know the leakage area, pipe leakage rate, and the number of leaks in pipe area if there is a water flow rate decrease. The data is processed with an NodeMCU microcontroller based on Internet of Things (IoT). The accuracy of all water flow sensors after calibration is 97,53%. When testing with the determination of each leaked area the results are appropriate. The reading of each water flow rate decrease that occurs has an accuracy of determiningthe leakage rate of 90,2% while the suitability of reading the number of leakage areas depends on the detection of the leakage area and the classification of the leakage rate. The greater the water flow reads on the sensors, the precission level to determine the level of water pipe leakage is getting better, and vice versa, this is due to sensors having variable variations in flow rate readings.